The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10103-011-0923-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 940 nm light-emitting diode (led) on sciatic nerve regeneration in rats

Abstract: The objective of the present study was to evaluate the effect of 940 nm wavelength light emitting diode (LED) phototherapy on nerve regeneration in rats. Forty male Wistar rats weighing approximately 300 g each were divided into four groups: control (C); control submitted to LED phototherapy (CLed); Sciatic Nerve Lesion without LED phototherapy (L); Sciatic Nerve Lesion with LED phototherapy (LLed). The lesion was caused by crushing the right sciatic nerve. A dose of 4 J/cm(2) was used for ten consecutive days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 42 publications
2
18
1
1
Order By: Relevance
“…LEDT's lack of regenerative effects presented herein differs from literature results, in which LEDT (940 nm, 4 J/cm 2 ) has been proven to stimulate the repair process of the calcaneal tendon in rats (640 nm, 20 J/ cm 2 ) (Bastos et al, 2009;Casalechi et al, 2009), as well as the morphofunctional recovery after SNC in rats (940 nm, 9.5 mW, 4 J/cm 2 ) (Serafim et al, 2012). The apparent contradictory results are probably due to the differences in doses, i.e., 20 and 4 J/cm 2 , which are more intense than the 2.5 J/cm 2 used in our study.…”
Section: Effect Of Ledt On Morphological and Motor Functional Neuronacontrasting
confidence: 91%
See 1 more Smart Citation
“…LEDT's lack of regenerative effects presented herein differs from literature results, in which LEDT (940 nm, 4 J/cm 2 ) has been proven to stimulate the repair process of the calcaneal tendon in rats (640 nm, 20 J/ cm 2 ) (Bastos et al, 2009;Casalechi et al, 2009), as well as the morphofunctional recovery after SNC in rats (940 nm, 9.5 mW, 4 J/cm 2 ) (Serafim et al, 2012). The apparent contradictory results are probably due to the differences in doses, i.e., 20 and 4 J/cm 2 , which are more intense than the 2.5 J/cm 2 used in our study.…”
Section: Effect Of Ledt On Morphological and Motor Functional Neuronacontrasting
confidence: 91%
“…Conversely, LEDT analgesic effect has not been investigated in pre-clinical models of pain. Nevertheless, LEDT presented anti-inflammatory activity and has reduced the expression of TNF-a in a rabbit osteoarthritis model (Oshima et al, 2011), decreased the levels of TNF-a and IL-1b mRNA at the site of calcaneal tendinitis in rats (Xavier et al, 2010a); inhibited the expression of cyclooxygenase-2 and prostaglandin E2 and pro-inflammatory cytokines in vitro (Lim et al, 2007;Choi et al, 2012); as well as stimulated morphofunctional recovery after SNC in rats (Serafim et al, 2012). Moreover, Costa et al (2008) demonstrated that LEDT when applied to acupuncture points was effective -at varying degrees -in the treatment of 15 patient with chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…Dentre as terapias atualmente em destaque, temos a fototerapia com LED (light-emitting diodediodo emissor de luz). Estudos tem descrito que a LEDterapia está associada com aceleração no processo de cicatrização de feridas na pele, melhora na recuperação de lesão por isquemia no coração e até atenuação na degeneração do nervo óptico lesionado (SERAFIM et al, 2012;HEMMINGS et al, 2017). Atribuem-se parte dos efeitos do LED à estimulação na função mitocondrial, neste contexto, estudos in vitro e in vivo, sugeriram que o LED é capaz de estimular as funções mitocondriais por aumentar o consumo de oxigênio, a produção de ATP, o transporte de elétrons e por promover redução na formação de espécies reativas do oxigênio e ainda minimizar reações inflamatórias, possivelmente por interferir na geração/ação da citocina TNFα.…”
Section: Issn 1809-3957unclassified
“…The application of light, by sources of low-level laser or lightemitting diode (LED), has been widely studied in health sciences and potentially aids the prevention and recovery of injuries, as well as anti-inflammatory and analgesic effects, although the influence on human exercise, as well as sportrelated context, as injuries, soreness, training recovery, rehabilitation, and performance enhancement, should be better explored [1][2][3]. Moreover, little theoretical bases were found to support LED as ergogenic aid for oxidative phosphorylation metabolism response.…”
Section: Introductionmentioning
confidence: 99%